Estimates of Present‐Day and Future Climatologies of Freezing Rain in Europe Based on CORDEX Regional Climate Models. Issue 23 (11th December 2018) - Kämäräinen, Matti; Hyvärinen, Otto; Vajda, Andrea; Nikulin, Grigory; Meijgaard, Erik van; Teichmann, Claas; Jacob, Daniela; Gregow, Hilppa; Jylhä, Kirsti
Abstract: The effects of climate change on freezing rain in Europe under medium (RCP4.5) and strong (RCP8.5) future emission scenarios were assessed using seven regional climate model simulations conducted within the World Climate Research Project's COordinated Regional climate Downscaling Experiment over the European Domain (EURO‐CORDEX). A precipitation‐typing algorithm was applied to modeled three‐dimensional subdaily time series of key meteorological variables to estimate the occurrence and amounts of freezing rain above selected intensity thresholds. The annual probabilities of freezing rain during the baseline (1971–2000) and future (2071–2100) periods were calculated. The models agree that under the RCP8.5 scenario, the frequencies of freezing rain decrease in western, central, and southeastern Europe by 20–55% and increase in the northern and northeastern parts of the continent by 0–50% toward the end of the century. In the northern regions, the peaks in spring and fall with freezing rain amounts during the baseline period tend to merge to a single peak in winter during the future period. Under the RCP4.5 scenario, the changes are qualitatively similar but smaller. Key Points: Freezing rain increases in northern Europe and decreases in central Europe toward the future Location‐dependent climate change signals in seasonality of freezing rain were found Modeled vertical temperature profiles are likely to explain model‐based differences in results